1992
DOI: 10.1177/074193259201300110
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Cultural-Organizational Perspective in Exclusion of Youth with Social Maladjustment

Abstract: This article reviews the problem of exclusion from special education of children or youth with social maladjustment, but expands the conceptualization by placing it in the context of the historical need to limit services to children or youth with emotional or behavioral disorders and the current underidentification of such pupils. Definitional issues that tend to confuse the debate, at both the micro-and macroperspective level, are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Despite continuing concerns about its eligibility criteria (cf. Algozzine et al, 1979; The Executive Committee of the Council for Children with Behavioral Disorders, 1987; Forness, 1992a, 1992b; Forness & Kavale, 2000; Forness & Knitzer, 1992; Mattison, 2015; McIntyre, 1993; Merrell & Walker, 2004), the definition appears to have been acceptable to special education professionals. Simply put, it has remained essentially the same across the history of efforts to provide services to students with behavioral problems in school that cannot be attributed to the intellectual, sensory, or health factors that define the other categories of special education.…”
Section: Defining Emotional Disturbance and Identifying Disturbed Behmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite continuing concerns about its eligibility criteria (cf. Algozzine et al, 1979; The Executive Committee of the Council for Children with Behavioral Disorders, 1987; Forness, 1992a, 1992b; Forness & Kavale, 2000; Forness & Knitzer, 1992; Mattison, 2015; McIntyre, 1993; Merrell & Walker, 2004), the definition appears to have been acceptable to special education professionals. Simply put, it has remained essentially the same across the history of efforts to provide services to students with behavioral problems in school that cannot be attributed to the intellectual, sensory, or health factors that define the other categories of special education.…”
Section: Defining Emotional Disturbance and Identifying Disturbed Behmentioning
confidence: 99%
“…We published the article in the context of a need to operational criteria for special education definitions and in the hope of addressing the nagging concerns related to who was and who should be receiving services for emotional disturbance, and the potential stigma associated with being labeled (cf. Clarizio, 1992; Forness, 1992a, 1992b, 1996; Kauffman & Badar, 2013; Mercer, Forgnone, & Wolking, 1978; Olympia et al, 2004; Yard, 1977; Ysseldyke, Algozzine, & Thurlow, 1982). My interest in definitions grew from my experiences teaching “educable mentally retarded,” “disabled reader,” and “emotionally disturbed” (as they were known at that time) students.…”
mentioning
confidence: 99%
“…Although schizophrenia was included, the SED definition 'does not include children who are socially maladjusted, unless it is demonstrated that they are seriously emotionally disturbed.' Since social maladjustment was not given specification in the law, it came to be defined in terms of disruptive and antisocial behavior (Forness, 1992b). Generally, such behavior is often equated with conduct disorder (CD) characterized by a persistent pattern of behavior violating basic rights of others or ageappropriate social rules (APA, 1994).…”
Section: Definitions Of Emotional or Behavioral Disordersmentioning
confidence: 99%
“…Symptoms include a variety of aggressive, destructive, dishonest, or noncompliant behaviors (Kazdin, 1995). Given these parameters, it seems illogical to exclude students because their problems are considered to be 'merely' CD (Center, 1990) while the actual underlying emotional disorders may not be recognized because the more evident 'social maladjustment' is excluded (Forness, 1992b). Clearly, social maladjustment may be evidenced in the federal definitional criteria (especially b and/or c) which, in fact, were originally meant to be indicators of social maladjustment (Bower, 1982).…”
Section: Definitions Of Emotional or Behavioral Disordersmentioning
confidence: 99%
“…The perplexing dilemma for many school systems across the nation is properly identifying those students who are in need of special education services. Unfortunately, determining eligibility for special education under the classification of emotional disturbance (ED) and ensuring the provision of a free appropriate public education in accordance with the Individuals With Disabilities Education Act (IDEA) has been persistently difficult given a host of controversial issues surrounding current eligibility criteria and the poor outcomes experienced by this population (Bradley, Doolittle, & Bartolotta, 2008; Forness, 1992; Maag & Howell, 1992; Sanford et al, 2011; Smith, Katsiyannis, & Ryan, 2011; Wagner, Kutash, Duchnowski, Epstein, & Sumi, 2005; Zhang, Katsiyannis, & Herbst, 2004).…”
mentioning
confidence: 99%